ANALISIS KANDUNGAN β-KAROTEN FUSAN INTRASPESIES Chlorella vulgaris dan APLIKASINYA SEBAGAI PAKAN TAMBAHAN PADA POST LARVA STADIA 10 UDANG WINDU (Penaeus monodon). - Dwi Kristyaningrum; Hermin Pancasakti Kusumaningrum; Endang Kusdiyantini (Jurnal Akademika Biologi, 2013)
Carotenoids are one of pigment which needed for development of post-larvae tiger shrimp (Penaeus monodon), but the shrimp unable to synthesis carotenoids by themselves in the body so it takes a feed containing carotenoids. Carotenoids can be obtained from synthetic feed or natural feed. One of the natural feed is microalgae Chlorella vulgaris. β-carotene is the highest content of carotenoid in C. vulgaris, this content can be improved by protoplast fusion. The purpose of this study was to determine the amount of β-carotene in fusan intraspecies C. vulgaris and it’s application as supplement in the post-larvae stadia 10th tiger shrimp (P. monodon) Measurement of the amount of  β-carotene using UV-Vis at a wavelength of 460nm. The feeding is done three times a day. The results showed that the amount of β-carotene on fusan C. vulgaris is greater than the wildtype of C. vulgaris. β-carotene in the fusan C. vulgaris is14.88µg/g while the wildtype of C. vulgaris is 7.14 µg/g. Additional applications C. vulgaris by 10 x 104 in 0.0225 g synthetys feed post-larvae stadia 10th shrimp (P. monodon) compared to the post-larvae shrimp fed only control showed that the feed given additional fusan of C. vulgaris increases the weight of shrimp at 39.9%, while the given wildtype of C. vulgaris increasing shrimp weight by 10.1%. Keywords: β-carotene, Chlorella vulgaris, protoplast fusion, post larvae shrimp